A FORMAÇÃO DE UM VÍNCULO AFETIVO ENTRE EDUCADORAS E CRIANÇAS COMO POSSIBILIDADE PARA UMA ADAPTAÇÃO FELIZ A CRECHE - Suélen Cristiane Marcos; Gilza Maria ZauhyGarms (Universidade do Oeste Paulista, 2016)
This work is the result of a cut of a doctoral research in progress, and aims to identify strategies to promote children's adaptation to day care used by professionals of early childhood education. The research is part of the mode type case study, a qualitative approach, involving discussions on the inclusion of children to day care, and the establishment of partnership between families and Early Childhood Education institutions for the successful adaptation of small children and the quality of early childhood education. The research field is an institution, public PresidentePrudente, which serves 182 children from 4.5 months to 3 years. The data collection procedures were semi-structured interviews addressed to 11 educators and 7 teachers. Results clarify that professionals point as essential to the success of children's adaptation to day care the formation of an emotional bond between educators, teachers and children.